Mea culpa : lessons on law and regret from U.S. history - Bender, Steven (New York : New York University Press, 2016)
In 'Mea Culpa', Steven W. Bender examines how the United States' collective shame about its past has shaped the evolution of law and behavior. We regret slavery and segregationist Jim Crow laws: we craft our legislation in response to that regret. By examining policies and practices that affected the lives of groups that have been historically marginalized and oppressed, Bender is able to draw persuasive connections between shame and its eventual legal manifestations.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 12, 2016).
Keywords: Human rights -- United States -- History; Regret -- Political aspects -- United States -- History; Minorities -- Legal status, laws, etc. -- United States -- History; Discrimination -- Law and legislation -- United States -- History; Marginality, Social -- Political aspects -- United States -- History; United States -- Social policy -- Moral and ethical aspects; United States -- Emigration and immigration -- Government policy -- Moral and ethical aspects; Society; United States of America, USA; History of the Americas; Jurisprudence & general issues; Legal history